'A walk for Africa' : combating the demon of HIV / AIDS in an African Pentecostal Church - the case of the Redeemed Christian Church of God : the challenge of HIV / AIDS to Christian theology - Adogame, Afe (Scriptura: International Journal of Bible, Religion and Theology in Southern Africa, 2005)
The HIV / Aids pandemic is one crisis that has catapulted the African continent into global limelight, particularly in the last decade. In spite of the common rhetoric whipped by the international community, prevention and impact mitigation responses have been largely hypocritical, half-hearted and grossly inadequate. The scourge seems to have defied any discernible medical, therapeutic and curative measures, thus leaving it to gradually erode the fabric of these societies. Religious groups have been largely affected, especially as youth, the highest HIV / Aids riskgroup, swell their membership. This shapes the responses of religious groups and poses a crucial challenge to their beliefs, ritual practices and worldviews. Using the example of the Redeemed Christian Church of God in Nigeria and Diaspora, this article demonstrates the various mechanisms employed to combat the epidemic. The RCCG conceptualization of disease and healing is central in understanding these responses and measures in combating HIV / Aids.
Free
Keywords: HIV / Aids; Pentecostal theology